Electrical Energy Efficiency : Technologies and Applications - Baggini, Angelo B.; Sumper, Andreas (Chichester [England] ; Hoboken, N.J. : Wiley, 2012)
"Provides up-to-date information on today's global policies, technologies and economic realities in a single, synergistic text"--
10.3.2. Selection of the most suitable electrotechnology 10.3.3. Increasing the efficiency of the existing electroheating equipment REFERENCES 11- HEAT, VENTILATION AND AIR CONDITIONING (HVAC) Roberto Villafafila-Robles, Jaume Salom 1. Basic concepts 2. Environmental thermal comfort 3. HVAC systems 3.1. Energy conversion 3.2. Energy balance 3.3. Energy efficiency 4. Energy measures in HVAC systems 4.1. Final service 4.2. Passive methods 4.3. Conversion device 4.4. Energy sources References 12 -- DATA CENTERS Angelo Baggini, Franco Bua 1 Standards 2 Consumption profile 2.1 Indici di prestazione energetica 3 IT infrastructure and equipment 3.1 Blade server 3.2 Storage 3.3 Network Equipment 3.4 Consolidation 3.5 Virtualization 3.6 Software 4 Facility infrastructure 4.1 Electrical infrastructure 4.1.1 UPS (Uninterruptible Power Systems) 4.1.2 PDU (Power Distribution Unit) 4.1.3 PSU (Power Supply Units) 4.1.4 Lighting 4.2 HVAC infrastructure 4.2.1 Cooling best practices 5 DG and CHP for Data Centres 6 Organizing for ENERGY Efficiency 7. References 13 -- REACTIVE POWER COMPENSATION Zbigniew Hanzelka, Waldemar Szpyra, Andrei Cziker, Krzysztof Piatek 13.1. Reactive power compensation in an electric utility network 13.1.1. Economic efficiency of reactive power compensation 13.2. Reactive power compensation in an industrial network 13.2.1. Linear loads 13.2.2. Group compensation 13.2.2. Nonlinear loads 13.3. VAR compensation 13.3.1. A synchronous condenser 13.3.2. Capacitor banks 13.3.3. Power electronic compensators/stabilizers Bibliography Index.
Includes bibliographical references and index.
Keywords: Electric power -- Conservation -- Standards; Energy conservation -- Standards; Energy dissipation; Electric power transmission -- Reliability; TECHNOLOGY & ENGINEERING -- Electrical; Electronic books